Genetic diversity analysis of selected Capsicum annuum genotypes based on morphophysiological, yield characteristics and their biochemical properties. (19th July 2018) - Ridzuan, Raihana; Rafii, Mohd Y; Mohammad Yusoff, Martini; Ismail, Siti Izera; Miah, Gous; Usman, Magaji
Abstract: BACKGROUND: Assessment of the different desirable characters among chili genotypes has expanded the effective selection for crop improvement. Identification of genetically superior parents is important in assortment of the best parents to develop new chili hybrids. RESULTS: This study was done to assess the hereditary assorted variety of selected genotypes of Capsicum annuum based on their morphophysiological and yield traits in two planting seasons. The biochemical properties, capsaicinoid content (capsaicin and dihydrocapsaicin), total phenolics content and antioxidant action determination of unripe and ripe chili pepper fruits were carried out in dry fruits. AVPP9813 and Kulai 907 were observed to have high fruit yields, with 541.39 and 502.64 g per plant, respectively. The most increased genotypic coefficient of variation (GCV) and phenotypic coefficient of variation (PCV) were shown by the fruit number per plant (49.71% and 66.04%, respectively). High heritability was observed in yield characters viz‐à‐viz fruit weight, length and girth and indicated high genetic advance. Eight groups were obtained from the cluster analysis. For the biochemical analysis, the capsaicinoid content and total phenolic content were high in Chili Bangi 3 at unripe and ripe fruit stages, while for antioxidant activity SDP203 was the highest in ripe dry fruit. CONCLUSION: Higher GCV and PCV, combined with moderate to high heritability and high hereditary progress, were seen in number of fruit per plant, fruit yield per plant and fruit weight per fruit. These findings are beneficial for chili pepper breeders to select desirable quantitative characters in C. annuum in their breeding program. © 2018 Society of Chemical Industry